Effectiveness of biofungicide formula on rhizome rot disease of red ginger and its plant growth - HUSDA MARWAN; ISLAH HAYATI; SRI MULYATI (Society for Indonesian Biodiversity, 2023)
Abstract. Marwan H, Hayati I, Mulyati S. 2023. Effectiveness of biofungicide formula on rhizome rot disease of red ginger and its plant growth. Biodiversitas 24: 2143-2148. Rhizome rot disease is a serious problem in red ginger cultivation in Indonesia. The development of organic red ginger cultivation to meet the demand for phytopharmaca raw materials requires a method of controlling rhizome rot disease without synthetic pesticides. The application of microbial biopesticides is one of the disease control methods that can be used to control rhizome rot disease in red ginger plants caused by Fusarium oxysporum. The purpose of this study was to determine the effect of biofungicide formula containing Trichoderma sp. TBP1 and Bacillus spp. (PBC25 and PBC32 isolates) on plant growth and disease incidence in red ginger. The results of in vitro testing showed that Trichoderma sp. (TBP1) isolate was able to inhibit the growth of F. oxysporum by 83%. The inhibition of F. oxysporum by Bacillus spp. isolates, namely PBC25 and PBC32 were 53.3% and 50%. It was observed that application of several biofungicide formulas containing Trichoderma sp. and Bacillus spp. on ginger rhizome before planting and 30 days after planting enhanced the growth of ginger plants and suppressed the development of rhizome rot disease between 78.57 - 93.3%.